1981
DOI: 10.1111/j.1440-6055.1981.tb01046.x
|View full text |Cite
|
Sign up to set email alerts
|

THE DISTRIBUTION AND RECOVERY OF AERIAL ULTRA‐LOW VOLUME SPRAYS FOR CONTROLLING NYMPHS OF THE AUSTRALIAN PLAGUE LOCUST, CHORTOICETES TERMINIFERA WALKER

Abstract: Field trials were conducted to determine the effect of a number of factors on the distribution and recovery of ULV spray droplets, emitted from a light aircraft equipped with Micronair rotary cage atomisers for the control of Australian plague locust nymphs [Chortoicetes terminijera (Walker)]. Spray deposits were sampled with small oil-sensitive papers attached to pasture vegetation, and were analysed with a Quantimet 720 Image Analyser for droplet number and volume densities.Results indicated that volume reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The trials have indicated that with the present technique of aerial nymphal control (Nguyen and Watt 1981), the vegetation cover in the treated area may need to be considered in the conduct of spray operations because of its effect on insecticide acquisition by the nymphs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The trials have indicated that with the present technique of aerial nymphal control (Nguyen and Watt 1981), the vegetation cover in the treated area may need to be considered in the conduct of spray operations because of its effect on insecticide acquisition by the nymphs.…”
Section: Discussionmentioning
confidence: 99%
“…Technical fenitrothion I .28 kg L-I was applied by a Cessna 185 aircraft equipped with 2 Micronair AU.3000 atomisers. The Micronair fan blades were set at 50' as in normal control operations (Nguyen and Watt 1981). Application was made at a speed of ca 190 km h-I and from a height of ca 5 m. Applied dosages were generally less than the recommended 0.3 L ha-' (0.38 kg ha-l a.i.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our selected dose of 90 mg kg −1 fenitrothion is ecologically realistic based on our knowledge that S. macroura can consume up to 100% of its body mass daily while gorge feeding and that locusts may contain residue values of up to 80 mg kg −1 fenitrothion after locust control operations . The dose selected for the present study is 3‐fold higher than previous research that found oxygen consumption rate to be unaffected by fenitrothion during both peak thermogenesis and exercise in a closely related species, S. crassicaudata .…”
Section: Methodsmentioning
confidence: 99%
“…Estimates have been made of the amount of insecticide acquired by both flying and settled locusts following aerial application at right angles to a light wind, using MicronaiP rotary cage atomisers (Symmons and Nguyen 1980; N. T. Nguyen unpublished data). The results used here are for a large atomiser blade angle since that produces a much higher recovery on settled targets (Nguyen 1979) as well as a greater collection by fliers (Symmons and Nguyen 1980). Curves have been fitted to allow the amount collected inpg/g of body weight, to be calculated for any time interval between the release of the spray and collection by the insect (Fig.…”
Section: Introductionmentioning
confidence: 99%